2018
DOI: 10.1038/s41598-018-22000-w
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear radiation effect on MHD Carreau nanofluid flow over a radially stretching surface with zero mass flux at the surface

Abstract: A mathematical model is envisaged to study the axisymmetric steady magnetohydrodynamic (MHD) Carreau nanofluid flow under the influence of nonlinear thermal radiation and chemical reaction past a radially stretched surface. Impact of heat generation/absorption with newly introduced zero mass flux condition of nanoparticles at the sheet is an added feature towards novelty of the problem. Further, for nanofluid the most recently organized model namely Buongiorno’s model is assumed that comprises the effects ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“… 9 , 10 , Lu et al . 11 , etc. Dual solutions were found for the unsteady flow over a shrinking sheet by Soid et al .…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 , Lu et al . 11 , etc. Dual solutions were found for the unsteady flow over a shrinking sheet by Soid et al .…”
Section: Introductionmentioning
confidence: 99%
“…During melting and freezing the of the thermal features of n-hexadecane containing inverse micelles of volume fractions was studied by Philip et al [22]. Lu et al [23] evaluated the combined effects of non-linear radiation and zero mass flux surface on the axisymmetric steady carreau nano-fluid induced by a radially stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Shahid et al demonstrated analytically (STSLM) the aftermath of magnetohydrodynamics (MHD) nanofluid drift holding microorganisms over a stretching surface. A mathematical rendition was provided by Lu et al to observe the steady MHD Carreau nanofluid drift under the conditions of chemical reaction and thermal radiation passed over a radically elongated regime. The outcome of double stratification on three‐dimensional (3D) convective nanoliquid drift over a stretchable (nonlinear) sheet was studied by Jagan et al via a perturbation mechanism, the effectiveness of the Dufour effect on a Casson nanoliquid was sinterrogated by Samrat et al Shojaei et al analytically discussed the Dufour and Soret effect on second‐grade non‐Newtonian fluid flow over a stretching cylinder.…”
Section: Introductionmentioning
confidence: 99%